PEMANFAATAN TEKNOLOGI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI TENGAH MASA PANDEMI COVID-19 BERBASIS SOCIAL DISTANCING DI SMKN 5 MALANG - Uun Almah; M Ilyas Thohari; Yorita Febry Lismanda (VICRATINA, 2020)
The Covid-19 pandemic, also known as Corona, is a plague that is contagious everywhere, covering large geographical areas. This virus is very fast transmission and has spread to various countries throughout the world, including Indonesia. And because the corona virus is very dangerous, the government requires people to be social distancing or keep a safe distance of at least two meters from others and avoid the crowd to prevent transmission of disease. This pandemic period also has an impact on the world of education, which is to avoid being exposed to the school virus held online (online learning). The existence of this article is to explain about school policies. the use of PAI learning technology, supporting and inhibiting factors and the results of the use of PAI learning technology in SMKN 5 Malang. This research uses descriptive qualitative method in which the researcher collects data through observation, interviews and documentation which will later be juxtaposed with the theories and ideas of experts. The conclusion from the results of this study is that schools implement online learning and provide Web-based learning facilities. But freeing each teacher to use other applications that are felt to be easier in the process of Teaching and Learning Activities (KBM). Utilization of PAI learning technology at Malang State Vocational School 5 uses Web-based learning technology, google classroom, edmodo, whatsapp which then centers on the homeroom teacher as an intermediary between the PAI teacher, students and guardians of students. The problem is that there are still teachers who have not mastered technology, while the biggest problem is inadequate student internet facilities due to limited economics and limited study time. The solution is Training with colleagues. Borrow friend facilities.Communicate with the teacher through WhatsApp. More intense in monitoring learning. Extend the learning period. The results of the use of PAI learning technology amid the social distancing-based Covid-19 pandemic at SMKN 5 Malang vary. The quantity can be said to be good, but in quality it is still taboo.